2014
DOI: 10.1016/j.jspd.2014.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Growing Rods Versus Magnetically Controlled Growing Rods for the Surgical Treatment of Early-Onset Scoliosis: A Case-Matched 2-Year Study

Abstract: Major curve correction was similar between MCGR and TGR patients throughout treatment. Annual T1-S1 and T1-12 growth was also similar between groups. The MCGR patients had 57 fewer surgical procedures than TGR patients. Incidence of unplanned surgical revisions as a result of complications was similar between groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
2
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(88 citation statements)
references
References 14 publications
(11 reference statements)
1
79
2
6
Order By: Relevance
“…A study comparing 12 MCGR-and TGRtreated patients demonstrated no significant difference in spine length gains, but there were 57 fewer surgical procedures in the MCGR group. 37 Although MCGR avoids the need for repeat surgical intervention for routine lengthenings, long-term data are not yet available for this technique. Similar to growth-friendly implants, the complication rate is high: 33% of patients treated with MCGR within 2 years of follow-up.…”
Section: Mcgrmentioning
confidence: 99%
See 1 more Smart Citation
“…A study comparing 12 MCGR-and TGRtreated patients demonstrated no significant difference in spine length gains, but there were 57 fewer surgical procedures in the MCGR group. 37 Although MCGR avoids the need for repeat surgical intervention for routine lengthenings, long-term data are not yet available for this technique. Similar to growth-friendly implants, the complication rate is high: 33% of patients treated with MCGR within 2 years of follow-up.…”
Section: Mcgrmentioning
confidence: 99%
“…Similar to growth-friendly implants, the complication rate is high: 33% of patients treated with MCGR within 2 years of follow-up. 37 …”
Section: Mcgrmentioning
confidence: 99%
“…In a growing rod construct, one or two rods are fixed to the screws or hooks above and below the scoliotic curve. The rods include mechanisms that enable incremental lengthening either by means of minimally invasive surgical access or noninvasively by means of transcutaneous application of magnetic forces (eg, with an external remote controller) (37).…”
Section: Rodsmentioning
confidence: 99%
“…In the first case matched study between traditional growth rods (TGR) and MCGR in 2014 by Akbarnia et al[28] they compared 12 MCGR patients to 12 case matched TGR patients. The average follow-up for TGR was 1.6 year more as compared to MCGR who had 2.5 year mean follow-up.…”
Section: What Is the Evidence?mentioning
confidence: 99%